Method for preparing PMI foam through composite foaming method
By using a composite foaming method that combines supercritical gas and gradient high-temperature chemical foaming, the problem of large and uneven pore size in PMI foam has been solved, achieving the preparation of PMI foam with high uniformity and low thermal conductivity, thus meeting the thermal insulation performance requirements in extreme environments.
Patent Information
- Application Number
- CN202511046185.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-25
AI Technical Summary
Traditional PMI foam has a large and unevenly distributed pore size, which limits its ability to improve thermal insulation performance. Furthermore, the manufacturing process lacks precision control, making it difficult to meet the requirements for ultra-low thermal conductivity.
A composite foaming method is adopted, combining supercritical gas foaming and gradient high-temperature chemical foaming. Supercritical gas forms a large number of cell sites in PMI foam, and the chemical foaming agent volatilizes or decomposes at high temperature, promoting cell growth and forming a uniform pore structure with an average pore size of less than 50µm, or even 10µm.
The PMI foam achieves uniformity in average pore size and pore size distribution, with a foaming ratio of over 15 times and a thermal conductivity reduced to below 0.023 W/(m·K), meeting the insulation requirements in extreme environments.
Smart Images

Figure CN121005946A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a method for preparing PMI foam using a composite foaming method. Background Technology
[0002] Polymethacrylimide (PMI) foam, due to its excellent specific strength, specific stiffness, heat resistance, and good dielectric properties, has been widely used as the core material in sandwich structures in aerospace, wind turbine blades, and high-speed trains. Its closed-cell structure also gives it certain thermal insulation properties. However, with increasingly stringent energy conservation and emission reduction requirements, and the growing demand for materials with ultra-low thermal conductivity in extreme environments (such as deep space exploration and liquefied natural gas storage and transportation), the thermal insulation performance of traditional PMI foam is no longer sufficient to meet higher requirements.
[0003] Currently, PMI foam is mainly prepared using chemical foaming. This method typically involves heating a copolymer or monomer mixture of methacrylic acid (MAA) and methacrylonitrile (MAN) containing a chemical foaming agent in a mold to initiate polymerization, crosslinking, and decomposition of the foaming agent, ultimately forming a foam structure. Meanwhile, supercritical fluid (SCF) physical foaming technology is also applied to prepare various polymer foams. This technology utilizes the dissolution and diffusion of supercritical fluids (such as CO2 and N2) in a polymer matrix, as well as the thermodynamic instabilities caused by sudden pressure or temperature changes, to achieve foaming. It offers advantages such as being environmentally friendly and easy to control the pore structure.
[0004] Despite some progress in existing technology, the following shortcomings still exist: Traditional chemically foamed PMI foams have large and unevenly distributed pore sizes: During the chemical foaming process, the nucleation and growth of bubbles mainly depend on the decomposition kinetics of the foaming agent and the viscoelastic behavior of the polymer matrix. It is difficult to precisely control the number of nucleation sites and the growth process, resulting in the final foam pore size typically ranging from several hundred micrometers, with a wide size distribution. The large pore size and uneven structure limit further improvement in its thermal insulation performance.
[0005] Challenges of pure supercritical fluid physical foaming (PMI): Although SCF physical foaming can prepare microporous or even nanoporous foams, its direct application to PMI systems, especially when foaming from in-situ polymerization of monomers or oligomers, faces the complex coupling problem of SCF solubility and diffusion coefficient in precursors with supercritical nucleation and chemical foaming agent cell growth, making it difficult to obtain ideal ultramicroporous structures, high closed-cell ratios, and high foaming ratios.
[0006] Limited improvement in thermal insulation performance: Due to the characteristics of its pore structure, the thermal conductivity of traditional chemically foamed PMI foam is usually above 0.030 W / (m·K), which is difficult to meet the application requirements for ultra-low thermal conductivity (such as <0.025 W / (m·K)).
[0007] Insufficient precision in process control: Traditional chemical foaming methods are sensitive to parameters such as temperature and foaming agent concentration. Even small process fluctuations can lead to significant differences in the performance of the final product, making it difficult to stably obtain PMI foam with a specific microporous structure (e.g., an average pore size of less than 100 micrometers). Summary of the Invention
[0008] The purpose of this invention is to overcome the above-mentioned technical defects and, through composite foaming technology, to prepare PMI foam with an average pore size of less than 50µm, or even reaching the 10µm level (ultramicropores), with a more uniform pore size distribution.
[0009] This invention is achieved through the following technical solution: A method for preparing PMI foam using a composite foaming method includes the following steps: Step A: Mix the reactive monomers, chemical foaming agents, crosslinking agents, and initiators thoroughly; Step B: Initiate activation at 30-70℃; Step C: Add the activated mixture into the mold, seal it, and carry out a bulk polymerization reaction at 30-70℃ to obtain the precursor; Step D: Place the precursor into a foaming mold, inject supercritical gas, pressurize to 3-50 MPa at 40-150℃, and maintain the temperature and pressure for 1-24 hours; Step E: Depressurize and perform the first foaming; Step F: Perform chemical foaming under gradient high temperature conditions.
[0010] Specifically, in step E, the pressure relief condition is to relieve the pressure to less than 3 MPa within 5 seconds, preferably to less than 1 MPa, more preferably to less than 0.5 MPa, and even more preferably to less than 0.2 MPa. Alternatively, the pressure can be directly relieved to atmospheric pressure (0.10-0.11 MPa). This can be a one-step pressure relief or a multi-step pressure relief.
[0011] After the pressure relief operation in step E, step F can be performed directly, or the curing time can be allowed to solidify for 0.1-12 hours before proceeding to step F. The specific curing time can be any value from 0.1 hours, 1 hour, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours, or a range between these values.
[0012] Specifically, in step F, the gradient high-temperature chemical foaming conditions are: first-stage chemical foaming at 80-140℃ for 0.5-4 hours, second-stage chemical foaming at 140-190℃ for 0.5-4 hours, and third-stage chemical foaming at 190-240℃ for 0.5-4 hours. Preferably, in step F, the gradient high-temperature chemical foaming conditions are: first-stage chemical foaming at 100-140℃ for 0.5-4 hours, second-stage chemical foaming at 140-180℃ for 0.5-4 hours, and third-stage chemical foaming at 190-220℃ for 0.5-4 hours.
[0013] Specifically, in step B, the activation time is 0.5-24 hours; the specific activation time can be any value or a range between 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, and 24 hours.
[0014] Specifically, the reaction time for step C is 24-72 hours; the specific reaction time can be any value or a range between 24 hours, 30 hours, 36 hours, 42 hours, 48 hours, 54 hours, 60 hours, 66 hours, and 72 hours.
[0015] The supercritical gas is selected from one or a mixture of two gases, namely carbon dioxide and nitrogen.
[0016] The reactant monomers are selected from 30-70 mol% acrylic monomers and 30-70 mol% acrylonitrile monomers, and 0-10 mol% of other comonomers may be added optionally; the molar content of the acrylic monomers can be 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, 46 mol%, 47 mol%, 48 mol%, 49 mol%, 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, 58 mol%, 59 mol%, 60 mol%, 61 mol%, 62 mol%, 63 mol%, 64 mol%, 65 mol%, 66 mol%, 67 mol%, 68 mol%, 69 mol%. The molar content of acrylonitrile monomers can be any value in mol%, 70 mol%, or a range between the two. This can be 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, 46 mol%, 47 mol%, 48 mol%, 49 mol%, 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, 58 mol%, 59 mol%, 60 mol%, 61 mol%, 62 mol%, 63 mol%, 64 mol%, 65 mol%, 66 mol%, 67 mol%, 68 mol%, 69 mol%, 70 mol%. The molar content of other comonomers can be any value in mol%, or a range between the two, and the molar content of other comonomers can be any value in 0 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, or a range between the two.
[0017] Specifically, the acrylic monomers are selected from methacrylic acid, acrylic acid, methyl methacrylate, ethyl methacrylate, methyl acrylate, and butyl acrylate; Specifically, the acrylonitrile monomers are selected from acrylonitrile and methacrylonitrile; Specifically, the other comonomers are selected from at least one of methacrylamide, acrylamide, bismaleimide, maleimide, allyl ester containing double bonds, allyl methacrylate, and butyl methacrylate.
[0018] The initiator is selected from oil-soluble free radical initiators, and the oil-soluble free radical initiator is selected from at least one of azo initiators and organic peroxide initiators; Specifically, the azo initiator is selected from at least one of azobisisobutyronitrile and azobisisoheptanenitrile; Specifically, the organic peroxide initiator is selected from at least one of benzoyl peroxide, dilauroyl peroxide, dicarbonate peroxide, and tert-butyl peroxide; The amount of initiator added is 0.1-3.5% based on the total weight of the reacting monomers; the amount of initiator added can be any value or a range between two of the following: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%.
[0019] The chemical foaming agent is selected from at least one of amide foaming agents, low-boiling-point organic compounds, and methacrylate foaming agents; The amount of chemical foaming agent added is 1-15% based on the total weight of the monomers; the amount of chemical foaming agent added can be any value or a range between 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0020] Specifically, amide-based foaming agents are selected from azodicarbonamide (ADC), carbamide, formamide, dimethylformamide, etc.
[0021] Specifically, low-boiling-point organic compounds are selected from ethanol, methanol, isopropanol, and low-boiling-point alkanes (such as n-pentane and isopentane).
[0022] Specifically, methacrylate foaming agents are selected from methyl methacrylate, ethyl acrylate, butyl acrylate, ethyl methacrylate, etc.
[0023] The crosslinking agent is selected from at least one of acrylamide crosslinking agents, allyl ester crosslinking agents containing double bonds, and maleimide crosslinking agents; The acrylamide crosslinking agent is selected from at least one of methacrylamide and acrylamide; The allyl ester crosslinking agent containing double bonds is selected from at least one of ethylene glycol dimethacrylate, allyl methacrylate, butyl methacrylate, butylene acrylate, and glycidyl acrylate. The maleimide crosslinking agent is selected from at least one of bismaleimide and maleimide; The amount of crosslinking agent added is 1-10% based on the total weight of the monomers; the amount of crosslinking agent added can be any value or a range between 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%.
[0024] A certain amount of other components can be added in step A, such as nucleating agent (0-2%), surfactant (0-1%), plasticizer (0-2%), and dielectric filler (0-10%).
[0025] The PMI foam prepared by the composite foaming method of this invention has an average pore size of less than 50µm (even reaching the 10µm level).
[0026] The present invention has the following beneficial effects: For macromolecules with rigidity and strong hydrogen bonds, such as PMI, foam materials prepared by supercritical foaming alone have a foaming ratio of no more than 2 times. When PMI foam is prepared by chemical foaming alone, the foaming ratio can reach more than 15 times, with an average pore size greater than 300 μm and uneven pore distribution.
[0027] To overcome the above-mentioned defects, this invention utilizes supercritical foaming technology as a physical foaming agent and nucleation promoter, which can form a large number of cell sites and promote the initial foaming of the material (not exceeding 2 times). During the subsequent gradient high-temperature foaming process, the chemical foaming agent volatilizes or decomposes to form gas pressure, which promotes the further growth of cells, ultimately forming PMI foam with an average pore size of less than 50µm, or even reaching the 10µm level (ultramicropores). The pore size distribution is more uniform, and even when the foaming ratio reaches more than 15 times, it can still meet the above-mentioned pore size requirements. Attached Figure Description
[0028] Figure 1 Comparative Example 4: Scanning electron microscope image of foam obtained by conventional chemical foaming.
[0029] Figure 2 Example 2: Scanning electron microscope image of foam obtained by composite foaming. Detailed Implementation
[0030] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0031] The raw materials used in this invention are commercially available.
[0032] Acrylic monomers: methacrylic acid; Acrylonitrile monomers: acrylonitrile; Chemical foaming agent: azodicarbonamide; Crosslinking agent: methacrylamide; Initiator: Azobisisobutyronitrile; Example: Method for preparing PMI foam using composite foaming: Step A: Mix the reactive monomers (molar percentages are shown in the table), chemical foaming agent (addition amount based on total monomer weight is shown in the table), crosslinking agent (addition amount based on total monomer weight is shown in the table), and initiator (addition amount based on total reactive monomer weight is shown in the table) evenly; Step B: Initiate and activate at 50°C for 2 hours; Step C: Add the activated mixture to a mold, seal, and carry out bulk polymerization at 45°C for 48 hours to obtain the precursor; Step D: Place the precursor into a foaming mold, inject supercritical carbon dioxide gas, pressurize to a set pressure (see table) at a set temperature (see table), and maintain the temperature and pressure for 4 hours; Step E: Depressurize to atmospheric pressure within 3 seconds and carry out the first foaming; Step F: Carry out chemical foaming under gradient high temperature conditions, the gradient high temperature foaming conditions are shown in the table.
[0033] Test methods: (1) Average pore size: High-resolution images of foam were captured using a scanning electron microscope (SEM), and the pore size and pore size distribution of the foam were measured using materials science foam size analysis software. The average pore size was calculated through statistical analysis.
[0034] (2) Pore uniformity: High-resolution images of foam were captured using a scanning electron microscope (SEM), and the pore size analysis software of materials science was used to measure the pore size and pore size distribution. The average pore size and pore size variance were calculated by statistics to characterize the pore uniformity.
[0035] (3) Foaming ratio: The apparent density of the unfoamed precursor (denoted as A) is measured by draining the valve, and the apparent density of the foam material (denoted as B) is measured. The foaming ratio = A / B.
[0036] (4) Thermal conductivity: "Determination of steady-state thermal resistance and related properties of thermal insulation materials - heat flow meter method" GB / T 10295-2008.
[0037] Table 1: Process parameters and test results of the composite foaming method in the examples and comparative examples Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 methyl methacrylate mol% 40 50 54 35 50 50 50 Acrylonitrile mol% 60 50 46 65 50 50 50 Chemical foaming agent % 8 15 3 10 15 15 15 Crosslinking agent % 3 1.4 3 5 1.4 1.4 1.4 Initiator % 0.2 0.15 0.2 0.1 0.15 0.15 0.15 Step D Temperature ℃ 120 140 70 120 140 140 140 Step D pressure (MPa) 15 8 18 15 8 8 8 First-stage chemical foaming temperature ℃ 100 140 120 130 80 100 120 First stage chemical foaming time h 2 0.5 1 1.5 0.5 0.5 0.5 Second-stage chemical foaming temperature ℃ 160 180 140 170 130 170 190 Second stage chemical foaming time h 3 2 3 1 2 2 2 Third-stage chemical foaming temperature ℃ 210 220 180 190 190 200 240 Third stage chemical foaming time h 1 2 3 1.5 2 2 2 Foaming ratio, times 15 20 5 14 20 20 20 Average pore size, µm 9.23 22.38 5.23 9.07 27.86 30.41 32.15 Pore size uniformity ±3.19 ±5.42 ±1.81 ±2.65 ±7.42 ±7.36 ±9.42 Thermal conductivity (W / (m·K)) 0.0233 0.0222 0.0277 0.0234 0.0237 0.0252 0.0263 As can be seen from Examples 2 / 5 / 6 / 7, at the same foaming ratio, Example 2 with the preferred chemical foaming process parameters has a smaller average pore size, better pore size uniformity, and better thermal insulation performance.
[0038] Continued from Table 1: Comparative Example 1 Comparative Example 2 Comparative Example 3 methyl methacrylate mol% 50 50 50 Acrylonitrile mol% 50 50 50 Chemical foaming agent % 15 15 15 Crosslinking agent % 1.4 1.4 1.4 Initiator % 0.15 0.15 0.15 Step D Temperature ℃ 165 120 120 Step D pressure (MPa) 15 15 15 First-stage chemical foaming temperature ℃ 140 70 150 First stage chemical foaming time h 0.5 2 2 Second-stage chemical foaming temperature ℃ 180 130 190 Second stage chemical foaming time h 2 3 3 Third-stage chemical foaming temperature ℃ 220 180 250 Third stage chemical foaming time h 2 1 1 Foaming ratio, times 15 10 30 Average pore size, µm 42.48 31.64 100.87 Pore size uniformity ±19.42 ±13.71 ±29.18 Thermal conductivity (W / (m·K)) 0.0312 0.0327 0.0306 Comparative Example 4: Method for preparing PMI foam by chemical foaming: Step A: Mix 50 mol% methacrylic acid, 50 mol% acrylonitrile, 15% azodicarbonamide, 1.4% methacrylamide, and 0.15% azobisisobutyronitrile evenly; Step B: Initiate activation at 50℃ for 2 hours; Step C: Add the activated mixture to a mold, seal, and carry out bulk polymerization at 45℃ for 48 hours to obtain the precursor; Step D: Perform chemical foaming under gradient high-temperature conditions: 130℃ for 1.5 h, 170℃ for 1 h, and 190℃ for 1.5 h. The foaming ratio is 15 times, the average pore size is 341 µm, the pore size uniformity is ±89 µm, and the thermal conductivity is 0.0335 W / (m·K).
[0039] As can be seen from Examples 1-7, when the expansion ratio of PMI foam obtained by the process of this application reaches 20 times, the average pore size can be controlled below 50µm. When the expansion ratio reaches 15 times, the average pore size can even be controlled below 10µm. Furthermore, the uniformity of the foam cells is good, which makes the PMI foam of this invention have excellent thermal insulation properties.
[0040] As can be seen from Comparative Examples 1-3, if the process parameters of physical foaming and / or chemical foaming are not within the scope of this application, it is difficult to obtain PMI foam with an average pore size of less than 10µm, or even less than 50µm, even when using a composite foaming method. Furthermore, the poor pore size uniformity of these PMI foams makes their thermal insulation performance inferior to that of the PMI foams in Examples 1-4.
[0041] As can be seen from Comparative Example 4, PMI foam obtained by conventional chemical foaming methods in this field has large pore size and poor pore size uniformity.
Claims
1. A method for preparing PMI foam using a composite foaming method, characterized in that, Includes the following steps: Step A: Mix the reactive monomers, chemical foaming agents, crosslinking agents, and initiators thoroughly; Step B: Initiate activation at 30-70℃; Step C: Add the activated mixture into the mold, seal it, and carry out a bulk polymerization reaction at 30-70℃ to obtain the precursor; Step D: Place the precursor into a foaming mold, inject supercritical gas, pressurize to 3-50 MPa at 40-150℃, and maintain the temperature and pressure for 1-24 hours; Step E: Depressurize and perform the first foaming; Step F: Perform chemical foaming under gradient high temperature conditions.
2. The method for preparing PMI foam using the composite foaming method according to claim 1, characterized in that, In step E, the pressure relief condition is to relieve the pressure to below 3 MPa within 5 seconds, preferably below 1 MPa, more preferably below 0.5 MPa, and even more preferably below 0.2 MPa; the pressure relief can be either one-step pressure relief or multi-step pressure relief; after pressure relief in step E, the product is cured for 0.1-12 hours or step F is performed directly.
3. The method for preparing PMI foam using the composite foaming method according to claim 1, characterized in that, In step F, the gradient high-temperature chemical foaming conditions are: first-stage chemical foaming at 80-140℃ for 0.5-4 hours, second-stage chemical foaming at 140-190℃ for 0.5-4 hours, and third-stage chemical foaming at 190-240℃ for 0.5-4 hours; preferably, in step F, the gradient high-temperature chemical foaming conditions are: first-stage chemical foaming at 100-140℃ for 0.5-4 hours, second-stage chemical foaming at 140-180℃ for 0.5-4 hours, and third-stage chemical foaming at 190-220℃ for 0.5-4 hours.
4. The method for preparing PMI foam using the composite foaming method according to claim 1, characterized in that, In step B, the activation time is 0.5-24 hours; in step C, the reaction time is 24-72 hours.
5. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, The supercritical gas is selected from carbon dioxide, nitrogen, or a mixture of both.
6. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, The reactant monomers are 30-70 mol% acrylic monomers, 30-70 mol% acrylonitrile monomers, and 0-10 mol% other comonomers; the acrylic monomers are selected from methacrylic acid, acrylic acid, methyl methacrylate, ethyl methacrylate, methyl acrylate, and butyl acrylate; the acrylonitrile monomers are selected from acrylonitrile and methacrylonitrile; the other comonomers are selected from at least one of methacrylamide, acrylamide, bismaleimide, maleimide, allyl ester containing double bonds, allyl methacrylate, and butyl methacrylate.
7. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, The initiator is selected from oil-soluble free radical initiators, and the oil-soluble free radical initiator is selected from at least one of azo initiators and organic peroxide initiators; the azo initiator is selected from at least one of azobisisobutyronitrile and azobisisoheptanenitrile; the organic peroxide initiator is selected from at least one of benzoyl peroxide, dilauryl peroxide, dicarbonate peroxide, and tert-butyl peroxide; the amount of initiator added is 0.1-3.5% based on the total weight of the reactants.
8. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, The chemical foaming agent is selected from at least one of amide foaming agents, low-boiling-point organic compounds, and methacrylate foaming agents. The amount of chemical foaming agent added is 1-15% based on the total weight of the monomers.
9. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, The crosslinking agent is selected from at least one of acrylamide crosslinking agents, allyl ester crosslinking agents containing double bonds, and maleimide crosslinking agents; the acrylamide crosslinking agent is selected from at least one of methacrylamide and acrylamide; the allyl ester crosslinking agent containing double bonds is selected from at least one of ethylene glycol dimethacrylate, allyl methacrylate, butyl methacrylate, butylene acrylate, and glycidyl acrylate; the maleimide crosslinking agent is selected from at least one of bismaleimide and maleimide, and the amount of crosslinking agent added is 1-10% based on the total weight of the monomers.
10. The method for preparing PMI foam by composite foaming according to claim 1, characterized in that, Step A also includes nucleating agents, surfactants, plasticizers, and dielectric fillers.